Ostertagia trifurcata as a parasite of Bubalus bubalis - Silva, R. G da (Pesquisa Agropecuaria Brasileira, 2014)
The occurrence of Ostertagia trifurcata in the stomach of a water-buffalo, from the State of Pará, is reported; it seems that this species is found in the water-buffalo for the first time.